FAKTOR YANG MEMPENGARUHI IMPLEMENTASI SISTEM INFORMASI MANAJEMEN RUMAH SAKIT (SIMRS) TERINTEGRASI DENGAN MENGGUNAKAN MODEL HOT–FIT - Yusnaniningsi Yusnaniningsi; La Ode Muhamad Sety La Ode Muhamad Sety; Adius Kusnan (NHM PRESS, 2021)
Implementation of information systems in hospitals (SIMRS) is very important to achieve quality services. However, monitoring and evaluation need to be carried out to find out how the benefits of SIMRS in hospital work units are. Thus, it allows hospitals to develop SIMRS by considering the factors that influence and benefit the use of SIMRS. The case study approach was carried out using the Human, Organization, Technology–Fit (HOT-fit) framework introduced by Yusof in 2006. The study was conducted at Bahteramas Hospital with a sample size of 162 respondents. The results of the analysis show that there is an influence of information quality on the use of the SIMRS system, SIMRS system development, user satisfaction. The inhibiting factors include SIMRS not according to needs, the perception that using manual recording is easier and faster, the perception that the use of SIMRS adds to the workload, and SIMRS output is considered not relevant to user needs.